The Effect of Kahoot Online Media on Students’ Scores in Learning Personal Pronoun at Tenth Grade of SMAN 9 Kota Jambi - Bujing Angadida; Suyadi Suyadi (Universitas Batanghari Jambi, 2020)
This research was done to find the effect of Kahoot online media on students’ scores in learning personal pronoun at tenth grade of SMA N 9 Kota Jambi Academic Year 2020/2021. The researcher used a quantitative method and experimental design as the research methodology with random sampling. The purpose of this research was to find out whether there was any significant effect of kahoot online media on students’ scores in learning personal pronoun. The sample of this research was at tenth grade of SMA N 9 Kota Jambi.This study involved 60 students, there was consist of 30 students of control class (X IPS 2) and 30 students of experimental class ( X IPS 4) at tenth grade of SMA N 9 Kota Jambi academic year of 2020/2021 as the object of the study and divided into two classes. Students’ scores in learning personal pronoun is effect after treatment Kahoot online media which is proven with students’ score higher than before treatment. The average pre-test control class 37,1 and post-test control class 48,7. Average pre-test experimental class 41,5 and post-test experimental class 83,5. Kahoot online media makes learning process more interesting. The value of t-test higher than the value of t-table (26,11> 2,001). Based on the finding above, it can be concluded that Kahoot online media has a significant effect of students’ scores in learning personal pronoun at tenth grade of SMA N 9 Kota Jambi.Key Words : Kahoot, Online Media, Personal Pronoun